Integrated modeling of aerosol, cloud, precipitation and land processes at satellite-resolved scales. (May 2015) - Peters-Lidard, Christa D.; Kemp, Eric M.; Matsui, Toshihisa; Santanello, Joseph A.; Kumar, Sujay V.; Jacob, Jossy P.; Clune, Thomas; Tao, Wei-Kuo; Chin, Mian; Hou, Arthur; Case, Jonathan L.; Kim, Dongchul; et al.
Abstract: With support from NASA's Modeling and Analysis Program, we have recently developed the NASA Unified-Weather Research and Forecasting model (NU-WRF). NU-WRF is an observation-driven integrated modeling system that represents aerosol, cloud, precipitation and land processes at satellite-resolved scales. "Satellite-resolved" scales (roughly 1–25 km), bridge the continuum between local (microscale), regional (mesoscale) and global (synoptic) processes. NU-WRF is a superset of the National Center for Atmospheric Research (NCAR) Advanced Research WRF (ARW) dynamical core model, achieved by fully integrating the GSFC Land Information System (LIS, already coupled to WRF), the WRF/Chem enabled version of the GOddard Chemistry Aerosols Radiation Transport (GOCART) model, the Goddard Satellite Data Simulation Unit (G-SDSU), and custom boundary/initial condition preprocessors into a single software release, with source code available by agreement with NASA/GSFC. Full coupling between aerosol, cloud, precipitation and land processes is critical for predicting local and regional water and energy cycles. Highlights: NU-WRF is an observation-driven integrated land–atmosphere modeling system. The software is a NASA-oriented superset of the standard NCAR WRF software. Enhancements include a satellite simulator package, coupling and physics options. Maintained at NASA/GSFC in an SVN repository, software is available by agreement. Supports coupling studies for land, atmosphere, aerosols, clouds and precipitation.